DEVELOPMENT OF DERIVATIVE MARKET IN 2000-2012 - E. V. Vasina (Vestnik MGIMO-Universiteta)
At the end of XIX century futures exchange emerged, in the early 70-ies XX century - option exchange of financial derivatives. These exchanges gave a huge boost to the development of market of the operations with derivative financial instruments. In fact, in the 1970-1980-ies a new market segment was actually formed - the stock and financial derivatives. Trade in financial derivatives began in the OTC market, which accounts for most of the trade of derivatives. Today volumes of the OTC market of derivatives are several times greater than the volume of world trade and world GDP. From 2000 to 2007 derivative OTC market grew rapidly. In 2007-2008 there is a decline in trade of derivatives, but already in 2009 the world market of OTC derivatives returned to pre-crisis growth rates. Among all the instruments of the OTC market of derivatives swaps on interest rates stand out in the volumes, which even in the crisis of2007-2008 slightly, but increased. Analysis of indicators of the global OTC market of derivatives reveals the predominance of instruments on interest rates: their share in the total world market in 2012 amounted to about 77%. If we consider the structure of the OTC market of derivatives on type contracts, in 2012 most of the contracts (66%) belonged to the swaps. As regards the structure of the world market of exchange derivatives, in 2012 the options had the largest share - 54 %, futures accounted for 46 %. Among all the exchange instruments on interest rates held 92%.